Water collection techniques at very low flow rates including strong capillary effects. (June 2020) - Bissig, Hugo; Tschannen, Martin; de Huu, Marc
Abstract: Milli-, micro- and nano-flow calibrations are important in several areas of pharmaceutical, flow chemistry and health care applications where volumetric dosage or delivery at given flow rates are crucial for the process. After developing a facility for the micro-flow range, METAS has developed a facility for flow rates from 50 nL/min up to 400 mL/min. The continuous collection of the flowing water into a beaker on a balance without having droplet formation for a continuous increase of the weighing values is a challenge (dynamic gravimetric method). This technique is often used to determine the flow rate over several orders of magnitude. In this paper, we describe the newly developed METAS piston provers and focus on the water collection techniques used for the flow rate determination of very low flow rates going as low as 50 nL/min by means of the dynamic gravimetric method. One water collection technique is to immerse the outlet needle into the water in the beaker. To reduce evaporation either a saturated environment is created or a layer of oil is added on top of the water. Another water collection technique is applied at the METAS facilities, where the outlet needle is positioned just over glass filters on top of the beaker to collect the water by means of a constant water bridge obtained independently of the flow rate. These two techniques are investigated for comparing the stability of the flow rate determination and the influence of the capillary forces acting due to the water or water-oil surface on the outlet needle and on the water bridge between the outlet needle and glass filters. The technique applied at METAS with the water bridge between outlet needle and glass filter reveals to be more stable for the flow rate determination and corrections due to capillary forces acting on the outlet needle can be neglected compared to the water collection technique with the immersed needle. Highlights: METAS piston provers have the ability to measure with any process-oriented liquids. Continuous collection of liquid in a beaker is an issue for dynamic gravimetric methods. Four different water collection techniques and their influence factors are described. Maintain a constant contact level of the liquid on the outlet needle.